Inherent porous structure modified by titanium dioxide nanoparticle incorporation and effect on the fouling behavior of hybrid poly(vinylidene fluoride) membranes. Issue 14 (21st December 2015) - Younas, Hassan; Shao, Jiahui; Bai, Hongwei; Liu, Liyan; He, Yiliang
ABSTRACT: The incorporation of nanoparticles (NPs) into a casting solution is a widely used practice for controlling the membrane fouling tendency, but the specific role of NPs in fouling control from an internal porous structure optimization has seldom been investigated. In this study, we evaluated the specific role of titanium dioxide (TiO2 )–NPs (Degussa P25) in mitigating membrane organic fouling. We prepared the membranes by tailoring the concentrations of the NPs well; this resulted in an optimized membrane microstructure consisting of fingerlike voids (beneath the skin layer of the membrane) and spongy voids (adjacent to the fingerlike voids). The NP incorporation induced the formation of spongy voids beneath the skin layer, and the increase in the NP concentration increased the formation of spongy voids. Moreover, surface images obtained by scanning electron microscopy, X‐ray photoelectron spectroscopy results, and contact angles confirmed that TiO2 –NPs were almost absent on the skin layer. Antifouling experiments were performed with a model organic foulant in two flow orientations [fingerlike voids facing the retentate (FVR) and spongy voids facing the retentate (SVR)]. The results show that the membrane fluxes in FVR decreased more than those in SVR. The membrane with 1.5 wt % TiO2 operated in SVR exhibited the lowest flux decline; this suggested that spongy voids with TiO2 exposure could mitigate fouling to a greater extent. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43265. Abstract :